PENGARUH PENCAMPURAN TANAH MINERAL BERPIRIT PADA TANAH GAMBUT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI - I Wayan Suastika; Supiandi Sabiham; Didi Ardi S (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2006)
Peat soil is one of the ecosystem having large potensial to be developed as a productive agricultural land if properly managed. Peat soil has constraints to plant growth such as physical, chemical, and biological properties. The application of mineral soil containing high pyrite content is expected to improve chemical characteristic of peat soil by bonding between cationic iron replenished mineral soil containing pyrite and phenolic acid ligand derived from peat soil. The objective of this experiment was to study the effectiveness of mineral soil containing pyrite incorporated by peat soils to the growth and yield of paddy rice. Experiment was done in a laboratory and green house of the Centre for Soil and Agroclimate Research and Development, Bogor using peat soil and mineral soil containing pyrite taken from Sugihan Kiri, Musi Banyuasin, South Sumatera. There are 13 treatments studied in the experiment, with 3 replications. Result showed that amelioration of peat soil applied by mineral soil with high content of pyrite, it’s potensial to improve the productivity of rice.